Conservation Status of Forest Birds in Isolated Forest Patches in Masbate, Philippines - Pagunutalan, Lisa Marie J.; Jakosalem, Philip Godfrey C.; Pedegrosa, Marisol G.; Catacutan, Mery Jean G.; Bueno, Reginaldo (Silliman Journal, 2022)
Bird surveys were conducted on the island of Masbate 1..)in July 2001 and on March 20-25, 2002. The study mainly focused on identifying the remaining lowland forests and determining their condition, as well as ascertaining the conservation status of the endemic and threatened birds of Masbate. Using deliberate search, mist-netting, and informal interviews, a total of 55 species (58%) of the birds previously known from the island were observed. Four new species for Masbate were recorded during the survey. Nine (56%) of the 16 Western Visayas endemic subspecies of birds known from Masbate were not seen and most are now possibly extinct on the island. The most significant result of the study was the finding of a remnant population of the Visayan Tarictic Hornbill Penelopides panini panini among sightings of the seven Masbate endemic subspecies_ Despite claims by locals that cockatoos ("white parrots") have been seen near the mangrove areas, the birds were not observed during the survey. Further study on other forest patches of Masbate Island may yet result in the discovery of significant populations of threatened and endemic species of birds.